Evalution Efficacy of some plants alkaloids in radial growth of Alternaria raphani which isolated from seeds and roots of Eggplant - Saadoon, Abdulamir S.; JeathomRoaÊ¼a A. (Al-Qadisiyah Journal of Pure Science, 2017)
This study included the efficacy of the atropine alkaloid , which extracted from fruits of Datura metel L. , and the solanine alkaloid which extracted from leaves of Solanum dulcamara L. and some fungicides on the radial growth of A. raphani and Fusarium solani isolated from seeds and roots of eggplant compare with fungicides Benomyl and Bluedil , and also testing the effect of these treatments in germination of seeds in sterilized and unsterilized soil , and detection of tested fungi by molecular method using Polymerase Chain Reaction (PCR) . the results showed that the alkaloids have significant effect for growth of tested fungus on soild culture medium (PDA) , in measuring with controlled treatment and tested fungicides at level of possibility 5 % , and also increasing the rate of germination of eggplant seeds in sterilized and unsterilized soil , and the concentration 15 mg/ml was the most effect among other concentrations and nearest to the action of fungicides . The testing of measuring Infra Red Spectrum (FTIR) showed the presence of many specific bands due to the extraction alkaloids.